Early and late implant loss among smokers according to a large-scale survey in Japan - Toru Nagao (Tobacco Induced Diseases, 2019)
Objective Oral implant loss has been recognized to be associated with smoking. Nicotine is affected by peri-implant soft tissue with vasoconstriction and impaired cellular healing response. However, a gap between preclinical and clinical research outcomes was observed. A cross-sectional, nationwide survey was conducted to examine the relationship between tobacco smoking and oral diseases among the Japanese population.